The Roles of Alkyl Branches of Ionic Liquid in the Corrosion Resistance of Pb/Sb/Sn Grids Alloy in Lead-Acid Battery - Behzad Rezaei; Ali Asghar Ensafi; Ahmad Reza Taghipour Jahromi (International Journal of Electrochemistry)
This paper describes the effects of ionic liquids (ILs) including mono, bicyclohexyl, and tetrahexyl ammonium hydrogen sulphate on the corrosion behaviour of Pb/Sb/Sn grids alloy of lead-acid battery with Pb, Sb (1.66 wt%), and Sn (0.24 wt%). Electrochemical behaviour has been investigated using Tafel plots and electrochemical impedance spectroscopy with various concentrations of ILs as electrolyte additives in 4.0 mol⋅L-1 sulphuric acid. The obtained results indicated that, by increasing number of alkyl or cycloalkyl branches in ILs, the corrosion rate of the lead alloy decreases, whereas inhibition efficiency shows a reverse effect. In the presence of all ILs in different concentrations, conversion current of PbSO4 to PbO2 (ia and ic) increases, while the reversibility, deduced from peak potential differences, decreases. Also, the effect of ILs adsorption model on the corrosion behaviour of electrode was proposed.